2012
DOI: 10.1002/marc.201100848
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cyclodextrin‐Mediated Ring Opening Polymerization of ϵ‐Caprolactone in the Presence of Yttrium Trisphenolate Catalyst

Abstract: Unmodified β-cyclodextrin has been directly used to initiate ring-opening polymerization of ϵ-caprolactone in the presence of yttrium trisphenolate. Well-defined cyclodextrin (CD)-centered star-shaped poly(ϵ-caprolactone)s have been successfully synthesized containing definite average numbers of arms (N(arm) = 4-6) and narrow polydispersity indexes (below 1.10). The number-average molecular weight (M(n,NMR)) and average molecular weight per arm (M(n,arm)) are controlled by the feeding molar ratio of monomer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[26][27][28][29] It has been found that many organolanthanide complexes are efficient initiators for the ring-opening polymeriza- tion (ROP) of ε-caprolactone. [20][21][22][30][31][32] To further explore the influence of the initiating group of organolanthanide complexes on the catalytic property, the catalytic behaviors of complexes 1-6 for the ROP of ε-caprolactone were tested (Scheme 2), and the results are listed in Table 3.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…[26][27][28][29] It has been found that many organolanthanide complexes are efficient initiators for the ring-opening polymeriza- tion (ROP) of ε-caprolactone. [20][21][22][30][31][32] To further explore the influence of the initiating group of organolanthanide complexes on the catalytic property, the catalytic behaviors of complexes 1-6 for the ROP of ε-caprolactone were tested (Scheme 2), and the results are listed in Table 3.…”
Section: Ring-opening Polymerization Of ε-Caprolactonementioning
confidence: 99%
“…Rare earth compounds exhibit excellent catalytic properties in ROP of lactones, lactides, , cyclic carbonates, cyclic ethers, and NCAs as well. We have reported polymerization of NCAs initiated by rare earth borohydrides [RE(BH 4 ) 3 (THF) 3 ] with quantitative yields and high MWs ( M n = 86.2 kDa) . The high catalytic activity of rare earth compounds makes them promising initiators for ROP of NTAs to produce high-MW polypeptoids.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the reactivity of the primary hydroxyl at C(6) position, AP [without a primary hydroxyl at its C(6) position] was also used to initiate the ROP of CL at the same reaction condition, but no polymer was obtained after post‐treatment. The theoretical computation of APT charges of AA reveals that the oxygen atom at C (6) position concentrates the most negative charge and the steric hindrance may also be one important influence on the reaction selectivity …”
Section: Resultsmentioning
confidence: 99%